2013
DOI: 10.1063/1.4819974
|View full text |Cite
|
Sign up to set email alerts
|

Elastic constants of polycrystalline L1-FePt at high temperatures

Abstract: Elastic constants of polycrystalline L1 0 FePt are studied from room temperature up to 1073 K by the electromagnetic acoustic resonance. The longitudinal-wave stiffness and the bulk modulus show intermediate values of polycrystalline Fe and Pt, but the shear modulus and Young's modulus show larger value than those of polycrystalline Fe and Pt. The Blackman diagram indicates that L1 0 FePt exhibits a tendency toward covalent-bond characteristic. Strong anharmonicity of the interatmoic potential is confirmed fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
(42 reference statements)
1
2
0
Order By: Relevance
“…It is also recognized that the decrease of the bulk modulus is demonstrated by a solid rhombus. Since both the values and temperature dependencies of bulk modulus reproduce the experimental results [37] with reasonable accuracy, we expect that the lattice softening effects on disorder-L1 0 phase equilibria is well introduced in this paper. We should point out, however, that more sophisticated vibrational free energy beyond quasiharmonic approximation is necessary for the systematic study of thermal properties above the Debye temperature, which is a future subject.…”
Section: B Lattice Thermal Propertiessupporting
confidence: 59%
“…It is also recognized that the decrease of the bulk modulus is demonstrated by a solid rhombus. Since both the values and temperature dependencies of bulk modulus reproduce the experimental results [37] with reasonable accuracy, we expect that the lattice softening effects on disorder-L1 0 phase equilibria is well introduced in this paper. We should point out, however, that more sophisticated vibrational free energy beyond quasiharmonic approximation is necessary for the systematic study of thermal properties above the Debye temperature, which is a future subject.…”
Section: B Lattice Thermal Propertiessupporting
confidence: 59%
“…Similar observations are reported by MacLaren et al [45] on the P4/mmm-FePt alloy. Moreover, using the Blackman diagram, Nakamura et al showed that P4/mmm-FePt exhibits a tendency toward covalent bond characteristics [46]. Furthermore, we note that the Pm-3m-FePt 3 system shows a trivial shallow pseudogap slightly below the Fermi energy, suggesting relative stability for this system.…”
Section: Density Of Statesmentioning
confidence: 48%
“…These results qualitatively agree with the existing experimental data: Fe bulk modulus measured at 300 K is equal to B 0Fe = 166.2 GPa 45 while Pt experimental bulk modulus at 300 K is equal to B 0Pt = 280 GPa 46 . Finally, a bulk modulus for FePt polycrystalline L1 0 structure recently measured at room temperature is equal to B 0FePt = 208.1 GPa 47 .…”
Section: Resultsmentioning
confidence: 90%